On the Stylistics and Translation Techniques of Mikołaj Rej’s Metrical Psalms - Kowalska, Danuta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
This analysis focuses on three of Rej’s earliest metrical translations of the psalms, composed before 1543: Psalm 85, Psalm 113 and Psalm 116, which were originally published as loose prints. The study aims to identify the characteristic features of Rej’s translation approach, with particular attention to those passages in the metrical psalms where the translator introduces semantic changes compared to the original text of the Vulgate. The article highlights the primary directions of these modifications, especially in relation to Rej’s subsequent work on the prose paraphrase of Psałterz (the Psalter). Comparative lexical analysis reveals that Rej frequently makes semantic alterations to update the content of the psalms. He also introduces amplifications to render the texts more concrete and to evoke a stronger emotional response from the readers. These techniques are similarly evident in his later prose paraphrase, Psałterz Dawidowy (the Psalter of David) (1543). The analysis thus illustrates the development and evolution of Rej’s editorial techniques as a translator.